Enforcement and Effectiveness of the Law - La mise en oeuvre et l'effectivité du droit General Contributions of the Montevideo Thematic Congress - Contributions générales du Congrès thématique de Montevideo (Ius Comparatum - Global Studies in Comparative Law,, 2018)
This book gathers the general contributions to the 3rd Thematic Congress of the International Academy of Comparative Law, which took place from 16 to 18 November 2016 in Montevideo, Uruguay. The main topic of the Congress was the enforcement and effectiveness of the law as a particularly relevant concern in today's society, in which the expressions of law have multiplied and legal pluralism seems to have reached its peak. The book addresses the enforcement of constitutional rights in national and supranational contexts, as well as the effectiveness of international dispute settlement. Further, it examines in detail the relations between the enforcement and effectiveness of criminal law, contract law and family law. Ce livre rassemble les contributions générales du 3ème Congrès thématique de l'Académie internationale de droit comparé, qui s'est déroulé du 16 au 18 novembre 2016 à Montevideo en Uruguay. Le sujet principal du Congrès était la mise en oeuvre et l'effectivité du droit qui constituent une préoccupation particulièrement pertinente dans la société contemporaine où les expressions du droit se sont multipliées et où le pluralisme juridique semble avoir atteint son apogée. Le livre traite de la mise en oeuvre des droits constitutionnels dans des contextes nationaux et supranationaux ainsi que de l'efficacité du règlement des différends internationaux. En outre, il examine en détail les relations entre l'application et l'efficacité du droit pénal, du droit des contrats et du droit de la famille. .